2013
DOI: 10.3109/02699052.2013.834381
|View full text |Cite
|
Sign up to set email alerts
|

The psychological effects of ostracism following traumatic brain injury

Abstract: These results are discussed in terms of the role of the negative experience of ostracism in motivating and guiding behaviour to re-establish group membership to prevent future social isolation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
1
4
2
Order By: Relevance
“…The TBI group displayed an overall similar pattern of needs fulfilment; however, only self-esteem and control remained significantly lower. This is inconsistent with the study of Kelly et al [12], where it was observed that control was not significantly affected in the TBI group whereas belonging was. Of particular significance to this study and in replication of a previous study [12], it was observed that the TBI groups' self-reported experience of ostracism was different to that of controls.…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…The TBI group displayed an overall similar pattern of needs fulfilment; however, only self-esteem and control remained significantly lower. This is inconsistent with the study of Kelly et al [12], where it was observed that control was not significantly affected in the TBI group whereas belonging was. Of particular significance to this study and in replication of a previous study [12], it was observed that the TBI groups' self-reported experience of ostracism was different to that of controls.…”
Section: Discussioncontrasting
confidence: 98%
“…This is inconsistent with the study of Kelly et al [12], where it was observed that control was not significantly affected in the TBI group whereas belonging was. Of particular significance to this study and in replication of a previous study [12], it was observed that the TBI groups' self-reported experience of ostracism was different to that of controls. That is, the TBI group self-reported less of an overall reduction in fundamental needs from when they were included to when they were excluded, and this result appears to lie in the TBI group feeling less included in the inclusion condition.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations